FNDC5/irisin reduces ferroptosis and improves mitochondrial dysfunction in hypoxic cardiomyocytes by Nrf2/HO‐1 axis. (23rd January 2022) - Cao, Guangying; Yang, Chao; Jin, Zhitao; Wei, Hanwen; Xin, Chao; Zheng, Chengrong; Xu, Jibing; Huang, Qing; Zhang, Zheng; Hu, Taohong
Abstract: Myocardial infarction is characterized by cardiomyocyte death and mitochondrial dysfunction induced by ischemia. Ferroptosis, a novel form of cell death, has been found to play critical roles under ischemic conditions. Recently, several studies have shown that fibronectin type III domain‐containing 5 (FNDC5) and its cleaved form, irisin, protect the heart against injury. However, its protective effect on ferroptosis and mitochondrial impairments is still unclear. Thus, our aim was to investigate the role of irisin in ferroptosis and mitochondrial dysfunction in cardiomyocytes under hypoxic conditions. Cardiomyocytes were treated with FNDC5 overexpression and/or irisin under normoxic and hypoxic conditions. Cell viability was assessed by Cell Counting Kit‐8 assay. Reactive oxygen species production was evaluated by dihydroethidium staining. In addition, the intracellular ferrous iron level (Fe 2+ ) and the relative concentration of malondialdehyde and ATP content were determined using an Iron Assay Kit, Lipid Peroxidation Assay Kit, and ATP Bioluminescent Assay Kit. The superoxide dismutase level in cells was measured using an Enzyme‐Linked Immunosorbent Assay Kit. Furthermore, an immunoblotting assay was used to determine ferroptosis‐related mitochondrial proteins. Hypoxia promoted cell death, increased ferroptosis, and caused mitochondrial dysfunction in cardiomyocytes. Interestingly, FNDC5 overexpression and/or irisin administration elevated cell viability, decreased ferroptosis, and reversed mitochondrial impairments induced by hypoxia. Mechanistically, FNDC5/irisin reduced ferroptosis and reversed mitochondrial impairments by Nrf2/HO‐1 axis in hypoxic cardiomyocytes. Thus, we have demonstrated that FNDC5/irisin plays a protective role in ferroptosis and mitochondrial dysfunction in hypoxia‐induced cardiomyocytes.